Copper-catalyzed 1, 6-conjugate addition of para-quinone methides with diborylmethane. Issue 16 (22nd June 2021) - Li, Xin; Gao, Guoliang; He, Songtao; Song, Qiuling
Abstract : Presented herein is the first 1, 6-conjugate addition of diborylmethane. This reaction features high yields, mild reaction conditions, and broad functional group compatibilities. Abstract : Presented herein is the first 1, 6-conjugate addition of diborylmethane, which is promoted by a simple and inexpensive copper catalytic system. This method features high yields, good selectivities and broad functional group compatibilities.